Growth and carcass mineralisation of Pacific whiteleg shrimp Penaeus vannamei Boone 1931 in response to water salinity - Jannathulla, R.; Dayal, J. Syama; Chitra, V.; Ambasankar, K.; Muralidhar, M. (Indian Journal of Fisheries, 2017)
The effect of water salinity (3, 10, 20, 30, 40, 50 and 60‰) on growth and proximate as well as mineral composition of Pacific whiteleg shrimp Penaeus vannamei was evaluated in a 45-day indoor trial. Significantly higher (p<0.05) growth was observed between 10 and 30‰ salinity, with specific growth rate and daily growth coefficient of 2.57-2.64 and 2.00-2.08 respectively. Poor survival of 26.66% was noticed at 60‰. Higher levels of protein and lipid as well as lower levels of moisture and ash were found in shrimp reared in high salinity water. Calcium level in whole shrimp was around 30 g kg-1 up to 30‰ and a gradual reduction was observed from 40 to 60‰ (23.49 to16.24 g kg-1). Sodium and potassium contents were significantly (p<0.05) higher and lower respectively in hyper saline reared shrimp carcass. Ca: P ratio was almost constant at 3:1 in shrimps reared up to 30‰ salinity and the ratio decreased beyond 30‰. The mineral profiles of water and shrimp were negatively correlated for calcium (-0.830), potassium (-708) and Ca: P ratio (-0.654). The present results indicate that potassium and magnesium supplementation may be helpful in low saline waters and limiting the mineral quantities in the diet especially calcium, magnesium, sodium and potassium may be advised for high salinity shrimp rearing.